Analisis Biaya Pemeliharaan dan Perawatan Kantor Pelayanan Bea dan Cukai Pekanbaru - Weno Dwi; Zainuri; Widya Apriani (JURNAL TEKNIK, 2020)
The existence of buildings has an important role in human life according to the purpose of the building. After completion of a building is expected to be able to carry out its functions according to the age of the plan. The purpose of this study is to estimate the cost of maintenance and care at the Pekanbaru Customs and Excise Service Office based on PERMEN NO.24 / PRT / M / 2008. It is expected that with this system, maintenance and maintenance activities will be in accordance with applicable standards and retain the use and value of the building. Regulation of the Minister of Public Works Number: 24 / PRT / M / 2008 concerning guidelines for building maintenance and maintenance, building maintenance This research was conducted using the Approximate Estimate method using the highest average unit price per m² of storey buildings for buildings accurate building as a guideline.he results of the calculation of this study found the estimated cost estimate of rough estimate (approximate estimate) of Rp. 16.156.679,93, - when compared with the calculation of the building price of Rp. 11.483.051,200 - the percentage of costs for maintenance of buildings in Pekanbaru Customs Service Office is only 0,1407% of the total price of the building, so that it can be categorized in the level of minor damage (<35%). Whereas the annual maintenance fee is Rp. 319.792.000,00, - in 2020 which is expected to increase every year based on the value of inflation based on Bank Indonesia. Keywords: Estimation, Maintenance, Maintenance, Offices spase